Pengaruh belanja modal urusan wajib dan urusan pilihan terhadap jumlah penduduk miskin dengan jumlah pengangguran sebagai variabel intervening di Provinsi Jambi - Rahmadi, Selamet; Hastuti, Dwi; Parmadi, Parmadi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The research aims to measure and analyze the increase in mandatory affairs capital expenditures, optional capital expenditures, the number and number of poor people in Jambi Province, and to measure and analyze the direct and direct effect of mandatory and optional capital expenditures on the number of poor people through the total movement of spending. As an intervention variable in Jambi Province. The data used are secondary in the form of a time series from 2008-2020. Direct effect: capital expenditure on mandatory affairs on the number of poor people has a positive and significant impact, capital expenditure on elective experiences on the number of poor people has a negative and significant effect, capital expenditure on mandatory affairs on the population has a negative and significant impact, capital expenditure on elective experiences on the number of movements has a positive effect and significant the number of poor people has a positive and significant impact. Indirect effect: capital expenditure on mandatory affairs on the number of poor people through the number of negative and significant effects (the number of components cannot be used as an intervention variable) and capital expenditure on elective affairs on the number of poor people through the number of trees has a positive and significant effect.